Desolation as a Plot: Urban Exploration on YouTube / Запустение как сюжет: «городские исследования» на YouTube - OLGA A. LAVRENOVA / ЛАВРЕНОВА О.А. (Наука телевидения)
The article analyzes and typologizes YouTube videos representing urban exploration (Urbex). This subculture, which gained popularity in the early 2000s, centers on the (often illegal) venturing into abandoned build-ings.4 Visual documentations of such penetrations, shared on YouTube, have played a crucial role in institutionalizing urbex, forging informational and visual connections that structured its previously spontaneous practice. Visu-ally, urbex videos can be considered as a symbiosis of amateur documen-tary and feature films created within a relatively limited set of plots. Despite the variety of locations explored, the videos consistently feature plotlines centered on narrative, action, discoveries of unsettling objects, mysticism, games (similar to walking simulators), and the creation of graffiti art. These plots reflect in various ways the ontological features of the subculture’s underpinnings: the confrontation with and challenges of overly regulated society, the perception of abandoned places and their exploration as a fron-tier between civilization and wilderness, the portrayal of derelict buildings as a paranormal Zone (a powerful image deeply ingrained in Russian cul-tural consciousness since Andrei Tarkovsky’s Stalker). There is also a place for creativity in the urbex subculture, which extends beyond making videos to transforming the environment—by adapting it for gameplay or using it as canvases for artistic works like large-scale graffiti, significantly altering the dull palette of these neglected urban buildings.